2023
DOI: 10.1155/2023/7754876
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Chronic Prostatitis or Chronic Pelvic Pain Syndrome: An Updated Systematic Review and Meta-Analysis

Abstract: Background. Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a complex male dysfunction, mostly seen in young and middle-aged men with a history of more than 3 months. As a traditional therapy of Traditional Chinese Medicine, acupuncture has been proven an effective method to treat CP/CPPS in recent years. Though some meta-analyses on acupuncture for chronic prostatitis were published in 2018 and 2019, most of the included studies were low in quality according to the JADAD score (JADAD < 4). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
2
0
3
Order By: Relevance
“…Although some meta-analyses on acupuncture for chronic prostatitis were published in 2018 and 2019, most of the included studies were low in quality. In this study, 9 electronic databases were searched from inception to March 1, 2022 21. The researchers included 11 trials (10 of them RCTs) of high-quality methodology involving 798.…”
Section: Miscellaneous Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some meta-analyses on acupuncture for chronic prostatitis were published in 2018 and 2019, most of the included studies were low in quality. In this study, 9 electronic databases were searched from inception to March 1, 2022 21. The researchers included 11 trials (10 of them RCTs) of high-quality methodology involving 798.…”
Section: Miscellaneous Conditionsmentioning
confidence: 99%
“…In this study, 9 electronic databases were searched from inception to March 1, 2022. 21 The researchers included 11 trials (10 of them RCTs) of high-quality methodology involving 798. Meta-analysis showed that compared with sham acupuncture and Western medicine, acupuncture played superior roles for CP/CPPS patients in the pain score, NIH-Chronic Prostatitis Symptom Index (NIH-CPSI) score, quality of life score, urinary symptom, and efficacy rate.…”
Section: Miscellaneous Conditionsmentioning
confidence: 99%
“…Die Inzidenz dieser komplexen neurologischen Dysfunktion nimmt von Jahr zu Jahr zu. Sie liegt weltweit bei etwa 9% und die Rezidivrate bei 20–50% 15 . Die Prävalenz liegt deutschlandweit bei ca.…”
Section: Chronischer Beckenbodenschmerzunclassified
“…In einem aktuellen systematischen Review untersuchten Pan et al 15 die Studienlage bzgl. des Einsatzes der Akupunktur bei CPPS/CP.…”
Section: Akupunkturbehandlung Bei Cpps/cpunclassified
See 1 more Smart Citation